(untitled) (CIPEEX, 2022)
A PHOTOGRAPHIC EXHIBITION OF SMILES IS ABLE TO SHOW THE GREAT DIVERSITY AND INEQUALITY, SINCE IT IS WELL KNOWN THAT SOCIAL INCLUSION HAS BEEN A SUBJECT QUITE ADDRESSED BECAUSE IT IS A METHOD OF COMBATING EXCLUSION THAT IS DIRECTLY RELATED TO THE INEQUALITIES, BE IT ECONOMIC OR SOCIAL, MAINLY OF GENDER AND RACE. WITH THE INCREASE OF INEQUALITIES, EXCLUSION AFFECTS THE QUALITY OF LIFE OF THE HUMAN BEING, AND KNOWING THAT HEALTH DEPENDS NOT ONLY ON THE ABSENCE OF DISEASES BUT ALSO ON THE QUALITY OF LIFE OF PEOPLE, INCLUDING THEIR LIVING CONDITIONS, WORK , ACCESS TO LEISURE, AMONG OTHERS, THE DENTIST HAS A FUNDAMENTAL ROLE IN THE FIGHT AGAINST INEQUALITIES TO ENSURE HEALTH AS A SOCIAL RIGHT OF ALL, CONSIDERING THAT ESTHETICS AND TOOTH LOSS ARE THE MAIN FACTORS THAT DIRECTLY AFFECT THE SOCIAL RELATIONS OF THE POPULATION DUE TO ITS NEGATIVE IMPACT ON SELF-ESTEEM. PHOTOGRAPHY IN THE FACE OF SOCIAL EXCLUSION MAY CONTRIBUTE TO FREEZING A MOMENT WHEN THERE IS A BLATANT EPISODE OF INEQUALITY THAT IS OFTEN NATURALIZED BY THE QUICK GLANCES OF DAILY LIFE. WITH THIS IN MIND, THE EXHIBITION AIMS TO RELATE PHOTOGRAPHY AND DENTISTRY THROUGH PHOTOS THAT SHOW THE DIFFERENT TYPES OF SMILES IN DIFFERENT PEOPLE WITH DIFFERENT CUSTOMS, DIFFERENT COLORS, RELIGIONS AND ECONOMIC CONDITIONS. TO OBTAIN THE PHOTOS, RANDOM PEOPLE AND / OR THE FAMILY OF THE WORK’S CONSTITUENTS WERE SELECTED, AFTER SIGNING AN AUTHORIZATION TERM IN WHICH THEY GUARANTEED THEIR ANONYMITY. THE EXHIBITION COUNTED ON A TOTAL OF FORTY THREE PHOTOGRAPHS THAT WERE REALIZED WITH THREE CAMERAS REVEALED IN SIZE 20X30 CM. THE EXPECTED RESULT WAS ACHIEVED, AS THE EXPOSURE OF THE VARIOUS SMILES ATTRACTED THE ATTENTION OF THE VIEWERS IN A POSITIVE WAY. IT IS CONCLUDED THAT, DESPITE THE GREAT DIVERSITY THAT EXISTS IN BRAZIL, IT IS POSSIBLE TO MAKE IT INSIGNIFICANT IN THE EYES OF THE BEHOLDER. KEYWORDS:DIVERSITY; PHOTOGRAPHY; INCLUSION; INEQUALITY.